If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = e + (e + 4) Reorder the terms: 0 = e + (4 + e) Remove parenthesis around (4 + e) 0 = e + 4 + e Reorder the terms: 0 = 4 + e + e Combine like terms: e + e = 2e 0 = 4 + 2e Solving 0 = 4 + 2e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-2e' to each side of the equation. 0 + -2e = 4 + 2e + -2e Remove the zero: -2e = 4 + 2e + -2e Combine like terms: 2e + -2e = 0 -2e = 4 + 0 -2e = 4 Divide each side by '-2'. e = -2 Simplifying e = -2
| 50-1.5x=1.5 | | .25x+.5=6.5-.75x | | 3(4+5x)=-168 | | -2y-19=0 | | s/4=4/8 | | 60-1.5x=1.5 | | 5-7/6x=3/2 | | s=1/4=4/8 | | 2(4x+7)+6x=5(x-10) | | 1/4=4/8 | | 2(8+6x)=124 | | 3(x+55)=33 | | A=12(B+b)h | | 0.8x+1.1=.05x-1 | | 45/48.15 | | [1/3]9CUBED | | 5x+10=15y | | 169=144+x^2 | | -7(7x-10)=609 | | 45/48.15=x/100 | | 1/3y=6-3x | | .4/.04 | | 400=m+310 | | 6(-3+x)=48 | | 4-5w=-6 | | a+-7+2a+-7+17+a+17=360 | | 221=m+76 | | -3(3x-1)=-7x-5 | | 15pt=c | | y=6x^2-4x-1 | | r/-164=50 | | 4m-3m+2m-m+3=2m+7-6+2 |